Design, Fabrication, and Performance Evaluation of Tractor Drawn Multi-Row Garlic Planter - Obsa, Girma (ASTU, 2021)
Garlic (Allium Sativum) Belongs To The Alliaceous Family, In The Same Family AsOnions. Garlic Is One Of The Most Important Crops Widely Cultivated Throughout The World Including Ethiopia. Garlic Is Widely Used As A Seed, For Consumption And Medicinal Purposes. Despite Wide Use, Many Problems Are Not Solved In The Production System, Among Which Planting Technique Seems The First. Due To The Lack Of A Garlic Planter System Farmers Still Use Traditional Methods For Planting Garlic Seeds, This Traditional Method Is Inefficient, Tiresome, Labour-Intensive, And Time Consuming. So By Providing Planting Machines The Above Problems Was Eliminated And Improve Planting Efficiency And Garlic Productivity. The Main Aim Of This Study Was To Design, Fabricate, And Evaluate The Performance Of A Tractor-Drawn Garlic Planter Capable Of Planting Garlic Seed. The Following Method Was Used, Studying Physical Properties Of Garlic Seed, Design All Of Component Parts,Fabrication, Performance Evaluation Of Garlic Planter, Data Collection, Data Organizing And Data Analysis To Draw Meaning Full Conclusion. The Developed Tractor Drawn Garlic Planter Consists Of Hopper, Feed Cup, Seed Metering Mechanism, Furrow Opener, Ground Wheel, Three-Point Hitch And Furrow Covering Device. The Physical Properties Of Two Varieties Of Garlic Were Studied. The Shape Index Of Two Varieties Was 0.78 And 0.755. The Angle Of Repose Of Two Varieties Was 26???And 25???. The Performance Of Tractor Drawn Garlic Planter Were Evaluated In The Laboratory And Field. Row To Row Spacing Can Be 30cm And Average Depth Of Seed Placement Was Found 5.97 Cm As Per Garlic Agronomic Requirement. The Seed Rate Was Calibrated And Observed That 122.86 Kg/Ha Which Is Laying In The Acceptable Range Of 100 To 140 Kg/Ha. The Field Test Conducted At Tractor Speed Of 36 Rpm Show 135.33 Kg/Ha Seed Rate. The Theoretical Field Capacity, Effective Field Capacity And Field Efficiency Of The Machine Were 0.38 Ha/Hr, 0.27 Ha/Hr And 72.52 % Respectively. The Average Germination Of The Metered Seed Was Observe 83.35% Seeds. The Tractor Drawn Garlic Planter Which Is Estimated To Be 16100.815 Ethiopian Birr, Then By Using Garlic PlanterMachine Farmers Can Save Time, Reduce Planting Operation Cost And Prevent Drudgery Of Labour. Making A Good Plat Form To Adopt The Planter To The Farmers To Use Garlic Planter Effectively And Efficiently.
Keywords: Garlic Planter, Design, Speed, Seed rate, Field test, Field efficiency, Performance